The Effect of Enhancing Ulvan's Antioxidant Properties in Supplemented Diets on Accelerating The Phenoloxidase Immune Response in White Shrimp - Azhar, Nuril; Yudiati, Ervia; Ambariyanto; Trianto, Agus (Bogor Agricultural University, Indonesia, 2024)
This study investigated the total phenol content (TPC) and DPPH inhibition of ulvan from Ulva lactuca, along with its supplementation effects on the specific growth rate (SGR) and phenoloxidase (PO) activity of Litopenaeus vannamei. Ulva lactuca samples were processed to obtain four ulvan extracts using different methods such as P-HWE (Polysaccharide-Hot Water Extract), O-HWE (Oligosaccharide-Hot Water Extract), P-A-HWE (Polysaccharide-Acid-Hot Water Extract), and O-A-HWE (Oligosaccharide-Acid-Hot Water Extract). The U. lactuca powder was treated with 80% ethanol overnight, then centrifuged and dried. Depigmented U. lactuca was extracted with water (65°C, 2 hours), and polysaccharides were precipitated with 99% ethanol, yielding P-HWE. P-HWE was heated at 145°C for 4.5 hours to yield O-HWE. Another extraction after depigmentation, using water containing H2O2 and ascorbic acid (65°C, 2 hours), precipitated P-A-HWE, which was dried and heated to yield O-A-HWE. FTIR analysis provided insights into the chemical composition and structural characteristics of ulvan extracts. TPC and DPPH inhibition were measured spectrophotometrically, and PO activity using a colorimetric assay with L-DOPA. Ulvan supplementation in shrimp feed was evaluated for growth and immune response. Results showed significant differences in TPC, DPPH inhibition, and PO activity among extracts, with O-A-HWE having the highest phenol content and DPPH inhibition. Ulvan supplementation significantly influenced the SGR of L. vannamei, with the highest SGR in the O-A-HWE treatment. This study suggests that ulvan extracts, especially O-A-HWE, could be effective natural immunostimulants for enhancing the health and growth of L. vannamei, warranting further research to optimize extraction methods and understand the underlying mechanisms.